Analysis of Basic Readiness in Ground Operations and Service as Preparation for an Internship at an Airport Cargo Terminal (Case Study: Yogyakarta STTKD Cadets) - Fauziah, Syifa (Peneliti.net, 2025)
Since the Ministry of Education and Culture launched the Independent Campus (MBKM) program, all universities in Indonesia have been encouraged to adapt their curricula to meet the needs of strategic government industries. One such program is the Independent Internship program, which requires a more extended period (4-6 months) than the 1-2 months of internships (PKL). During the implementation of PKL at the STTKD (Education and Training College), several findings emerged regarding dissatisfaction among users (the placement companies for PKL cadets) with the basic knowledge possessed by management program cadets. Therefore, an analysis of the basic knowledge readiness of management program cadets in ground operations and service is necessary to determine whether they align with the National Competency Standards (SKKNI) for the Transportation and Warehousing Category, specifically the Warehousing and Airport Activities, Ground Operations and Service Sub-Division. The research employed a quantitative approach with descriptive analysis techniques and simple linear regression to examine the 2018 management program curriculum achievements about SKKNI 226/2020. The research results showed that 23 Competency Indicators were needed for PKL Ground Operation and Service Air Logistic participants at the Airport Cargo Terminal before entering the field. Following the implementation of the 2018 curriculum, the CPMK Curriculum of the D4 MTU (Air Transport Management) and D3 MT (Transport Management) Study Programs had a 59.4% influence on the Competency Knowledge of SKKNI 226/2020 Ground Operation and Service Air Logistics. The remaining 40.6% of knowledge topics from the CPMK Curriculum needed adjustments to 10 D4 MTU and D3 MT Study Program courses to achieve the SKKNI 226/2020 competency.